Bennu's Natural Sample Delivery Mechanism: Estimating the Flux of Bennuid Meteors at Earth. Issue 9 (10th September 2021) - Melikyan, R. E.; Clark, B. E.; Hergenrother, C. W.; Chesley, S. R.; Nolan, M. C.; Ye, Q.‐Z.; Lauretta, D. S.
Abstract: NASA's OSIRIS‐REx mission observed millimeter‐ to centimeter‐scale pebbles being ejected from the surface of asteroid (101955) Bennu, indicating that Bennu is an active asteroid. About 30% of these particles escape from Bennu, and the minimum orbital intersection distance (MOID) between Bennu and Earth suggest the possibility of a "Bennuid" particle flux at Earth. We characterize the evolution of Bennu's particle stream and potential for meteor flux by simulating weekly particle ejections between the years 1780 and 2135 continuing their dynamical evolution until 2200. Ejections are modeled as a discrete release of 95 particles every week. The meteoroid stream is found to be fully distributed around Bennu's orbital path in 80 ± 40 years. Individual particles and streams remain associable to Bennu for the entire 420 years simulated. Particle flux at Earth is predicted to begin in 2101, as the Bennu‐Earth MOID reaches minimum values. The year of highest particle flux, 2182, experiences 161 Earth intersections and accounts for ∼ 1/4 of our predicted meteors. Our methods can be expanded to study the history and structure of the general meteoroid population and to estimate flux from specific near‐Earth asteroids. Plain Language Summary: NASA's OSIRIS‐REx asteroid sample return mission observed coin‐sized rock fragments launching from the surface of the near‐Earth asteroid Bennu. Although many of these particles fall back down to the surface of Bennu, about 30% escape the gravitational influence of this small celestial body and enter orbits around the Sun. By simulating the motion of small particles ejected from Bennu over the years 1780–2200, we test whether they eventually encounter Earth's atmosphere. The predicted particle flux ranges from undetectable to ∼ 1 meteor per 10 h, a rate which is comparable with the weakest known meteor showers. We find that ejected particles spread out along Bennu's orbit and occupy positions around the entire circle within 80 years. For the 420 years simulated, the particles can be easily associated with Bennu by the similarities in their orbits. Particles we simulated being ejected from Bennu are not found to impact Earth until 2101. We predict a maximum flux in the year 2182, with around 161 intersecting meteors potentially visible as shooting stars. Our methods can be used to investigate the possibility of meteoroid streams from other near‐Earth asteroids to identify sources of known meteoroid streams and meteor showers. Key Points: We simulate 355 years (1780–2135) of particle ejection from asteroid (101955) Bennu Meteor flux (at Earth) of particles from Bennu is < 1 / y r until 2100 AD, peaking in 2182 AD at 161 Bennuids The Bennu particle stream encircles in 80 years, and 99% of stream members remain associable for all 420 years of the simulation